Stary człowiek i pies - Mamzer, Hanna (Kraków: Akademia Ignatianum)
The article aims at analyzing a potential positive influence of animal assisted therapies on senior citizens. In the context of ageing, contemporary Western societies face a challenge of taking care of wellbeing of a growing number of their senior citizens. Not only should medical assistance be taken into account, but also adequate psychological support. Animal assisted therapies are still an undiscovered option of increasing a subjective sense of elderly person`s wellbeing.
Keywords: pies; starość; seniorzy; relacje; dog; senior citizens; animal assisted therapies